Cooperative Parenting Pasca Perceraian Perspektif Hukum Keluarga Islam - Ulum, M. Wildanul; Laili, Afrohatul; Azizah, Aisyatul; Latifah, Binti; Aini, Firda Syarifatul (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2025)
Divorce often leaves a significant psychological, emotional, and social impact on children, as well as disrupting their well-being and development. This study aims to explore Cooperative Parenting (Co-Parenting) as a way of post-divorce parenting that is in line with the principles of Islamic family law. This study uses a qualitative approach with a descriptive-analytical method based on literature study. The results show that effective Co-Parenting can minimize the negative impact of divorce by creating emotional stability, harmonious relationships, and consistent attention from both parents. This approach not only supports the physical and emotional needs of the child but also reflects the moral and spiritual responsibility of parents in accordance with Islamic values. The implementation of Co-Parenting has the potential to optimize children's development as well as be a strategic solution to maintain their welfare after divorce.